High-speed video observations of branching behaviors in downward stepped leaders and upward connecting leaders in negative natural lightning. (February 2019) - Wang, X.; Zhao, X.; Hao, Y.; Cai, H.; Liu, G.; Liao, M.; Qu, L.
Abstract: Branched downward stepped leader (DSL) associated with branched upward connecting leader (UCL) were observed together in one negative natural lightning. Branching behaviors and development scenarios of DSL and UCL have been investigated and compared with high-speed video frame sequence. The optical evidence provides that most of negative leaders exhibit branching tips, with four main branching points produced during propagation. The adjacent faint segments, which are likely the newly created channel sections after two adjacent space leaders have make connection with the leader tip, are simultaneously appeared ahead of negative leader tips; most of them could contribute to the tortuosity of leader channel and only few of them lead to the concurrent branches of channel, with the common root of significantly great luminosity. However, positive leaders normally do not have branched tips, but generating one branching point at early stage of UCL initiation even though the leader channel is rather faint. The two-dimensional (2D) average speeds of five negative branches and the main branch of UCL propagating are quite similar, ranging from 3.56 × 10 5  m/s to 3.89 × 10 5  m/s. Highlights: Branched positive and negative leaders were observed together in natural lightning. Most of negative leaders exhibit branched tips, but positive ones normally do not. Adjacent faint segments below negative leader tips have two development scenarios. Positive leaders generate one branching point at early stage of faint channel.